EFEITO MODERADOR DA CONCENTRAÇÃO DO CONTROLE ACIONÁRIO NA RELAÇÃO ENTRE O GERENCIAMENTO DE RESULTADOS E OS DIVIDENDOS: EVIDÊNCIAS DO MERCADO DE CAPITAIS BRASILEIRO - Silva, Vitor Correa da (2020)
This research aims to identify the moderating effect exerted by the shareholding concentration in the relationship between accruals earnings management and the dividends in the Brazilian public firms traded in [B]³. Considering that earnings management re